2015
DOI: 10.1073/pnas.1501967112
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic epigenetic regulation of glioblastoma tumorigenicity through LSD1 modulation of MYC expression

Abstract: The available evidence suggests that the lethality of glioblastoma is driven by small subpopulations of cells that self-renew and exhibit tumorigenicity. It remains unclear whether tumorigenicity exists as a static property of a few cells or as a dynamically acquired property. We used tumor-sphere and xenograft formation as assays for tumorigenicity and examined subclones isolated from established and primary glioblastoma lines. Our results indicate that glioblastoma tumorigenicity is largely deterministic, ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 73 publications
(77 reference statements)
3
58
0
1
Order By: Relevance
“…GBM is the primary and deadliest malignancy of the brain and extremely common (30)(31)(32) with near highest fatality in two years after diagnosis (33,34). The cellular capacity, which reconstitute the tumor entirely, and tumorigenicity of cell subpopulations are the major reasons of therapeutic failure (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GBM is the primary and deadliest malignancy of the brain and extremely common (30)(31)(32) with near highest fatality in two years after diagnosis (33,34). The cellular capacity, which reconstitute the tumor entirely, and tumorigenicity of cell subpopulations are the major reasons of therapeutic failure (31).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular capacity, which reconstitute the tumor entirely, and tumorigenicity of cell subpopulations are the major reasons of therapeutic failure (31). Growing evidence indicates cell subpopulations of GBM induce its lethality based on the properties of its tumorigenicity and self-renewal (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on studies of the GBM tumor microenvironment, it can be shown that GBM cells express cell surface molecules that suppress the immunologic function of microglia, while microglia reciprocally secrete specific cytokines to stimulate GBM growth [32]. These interactions are mediated in-part through secreted microvesicles, while PI3K γ regulates recruitment and protumor properties in microglia, suggesting a targetable strategy through inhibition of PI3K γ.…”
Section: Drug Targets and Cns Tumor Microenvironmentmentioning
confidence: 99%
“…Важно, что недостаток KDM1A увеличивает H3K4-триметилирование локуса онкогена MYC, активирующее его экспрессию при глиобластоме, и MYC-опосредованное изменение экспрессии транскрипционных факторов OLIG2 и SOX2 [87].…”
Section: (рис 2)unclassified